Determinants of Innovation Culture: a Study of Textile Industry in Santa Catarina - Giancarlo Gomes; Denise Del Prá Netto Machado; Joaquin Alegre (BBR: Brazilian Business Review)
The Brazilian textile industry has suffered the impact of products from Asian countries, mainly because of low prices. Seeking to determine the differential of the textile industry of the state of Santa Catarina, the objective of this study is to analyze the determinants of organizational culture –strategy, structure, support mechanisms, stimulus to innovation and communication –that influence innovation in textile companies in the state, based on a survey among 441 respondents from 16 firms. Data were analyzed using structuralequation modeling. We conclude that organizational structure was the dimension that had the strongest influence in shaping the culture of innovation. Flexibility and the presence of multifunctional teams are indicators that show that organizations are working to develop a culture of innovation.